Fiscal Regulations for Handling Inflation according to Taqiyyuddin An-Nabhani - Muhammad Sulthan Abimanyu Prakoso Putra (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
Inflation is a significant economic challenge in many countries, including Indonesia. In 2023, inflation in Indonesia reached 5.5%, far exceeding the target of 3±1%. Conventional economic systems often face difficulties in managing inflation, while Islamic economics offers alternative solutions. This study uses a literature study approach by analyzing the works of Taqiyuddin An-Nabhani, specifically in An Nizham Al Iqtishadi fi Al Islam and Al-Amwal fi Dawlat al-Khilafah. Data were collected from books, journals, and related literature discussing An-Nabhani's Islamic economic thought. The results show that An-Nabhani's proposed fiscal approach emphasizes the equitable distribution of wealth through instruments such as zakat and price regulation. This system can help reduce inflation by ensuring that wealth does not circulate in the hands of only a few people, while also protecting people's purchasing power. An-Nabhani emphasized the importance of the state's role in managing inflation through fiscal policies that focus on economic balance and wealth distribution. This fiscal policy must be combined with monetary policies that maintain the money supply, so that economic stability can be achieved. The main challenge is ensuring the effective implementation of wealth distribution policies in a modern economic context. Implementing An-Nabhani's theory requires structural reforms in the fiscal system, such as zakat management and tax reform. Furthermore, changes in economic behavior and global market dynamics pose challenges to the application of this theory. However, this approach offers the potential to reduce economic instability and create inclusive growth.